APPRAISAL DEVICES REALIZING ATTITUDES IN BARACK OBAMA’S INAUGURAL SPEECH - Ida Rohmawati (Universitas Islam Negeri Walisongo Semarang, 2016)
The purpose of this study was to describe and analyze Obama’s Attitudes towards phenomenon happened in America and the world realized in the speech using the Appraisal System Analysis. The speech analysis was done by breaking down the speech into several clauses and analyzing them to find out the Appraisal Devices and the types of Attitudes used. Analyzing the data, it could be inferred that the speech employed three kinds of Attitudes; Affect, Judgement, Appreciation. There were 323 clauses consist of 51 Af- fects, 155 Judgements, and 117 Appreciations. Positive Attitudes in the speech were used more than Negative Attitudes. Obama gave priorities to Positive Attitudes in presenting his speech because he was optimistic that the obstacles in his country would be solved and the condition of America would be better. The study revealed that Obama was a good orator with high capability and wonderful way of thinking.